A Cu2O@CuS@ZnIn2S4 double-layer core-shell structure photocatalytic material, a preparation method and application thereof

CN122999223APending Publication Date: 2026-10-30YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611408318.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但三种单一材料均存在性能短板,难以实现高效稳定产H2O2

Benefits of technology

[0036](1)本发明是将Cu(NO3)2·3H2O,L-抗坏血酸和C6H5O7Na3溶于去离子水中,搅拌30分钟,而后加入TAA溶液,最终产物分别用水和乙醇洗涤三次,随后在60°C真空干燥,得到具有立方体结构的Cu2O。将上述制备的Cu2O分散在去离子水中,超声搅拌,形成均匀分散的悬浮液后,随后加入TAA溶液,搅拌30分钟,获得核壳结构的Cu2O@CuS。最后,将上述制备的Cu2O@CuS分散在去离子水中,超声搅拌,形成均匀分散的悬浮液后。将Zn(CH3COO)2·2H2O和InCl3加入到分散液中,混合均匀后加入TAA溶液,混合物转移至聚四氟乙烯高压釜中,于180℃保持12小时。经自然冷却后,用水和乙醇洗涤产物,置于60℃真空烘箱中干燥,最终获得Cu2O@CuS@ZnIn2S4双层核壳结构光催化材料。本发明方法工艺简单,制备时间短,能耗低,制得的Cu2O@CuS@ZnIn2S4双层核壳结构光催化材料具有丰富的孔结构和大的比表面积。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999223A_ABST
    Figure CN122999223A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of photocatalytic preparation of H2O2, in particular to a Cu2O@CuS@ZnIn2S4 double-layer core-shell structure photocatalytic material and a preparation method and application thereof. Cu(NO3)2.3H2O, L-ascorbic acid and C6H5O7N3 are dissolved in deionized water, and a NaOH solution is added to the above solution under violent stirring, and Cu2O is obtained after stirring; Cu2O is dispersed in deionized water, and after ultrasonic stirring to form a uniformly dispersed suspension, Na2S.9H2O is added, and Cu2O@CuS is obtained after sulfidation etching; Zn(CH3COO)2.2H2O and InCl3 are dissolved in deionized water to form a uniform solution, and a thioacetamide solution is added drop by drop, and the like. The preparation process of the application is simple, easy to control and low in production cost, and the double-layer core-shell structure photocatalytic material prepared has the characteristics of high activity and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic preparation of H2O2, and in particular to a Cu2O@CuS@ZnIn2S4 double-layer core-shell structure photocatalytic material, its preparation method, and its application. Background Technology

[0002] Hydrogen peroxide (H2O2), as a green and efficient oxidant and clean energy carrier, is widely used in environmental remediation, chemical synthesis, medical and health care, energy storage, and many other fields, with market demand continuously increasing. Currently, the mainstream industrial method for preparing H2O2, the anthraquinone process, suffers from drawbacks such as complex processes, high energy consumption, significant pollution, and expensive equipment. Furthermore, the process easily generates byproducts, making it difficult to meet the demands of green chemical development. Photocatalytic H2O2 preparation technology relies on clean solar energy, offers mild reaction conditions, produces no secondary pollution, and is simple to operate. It represents a novel green technology to replace traditional industrial preparation processes, possessing extremely high research value and application prospects.

[0003] The core of a photocatalytic system is the photocatalytic material, whose performance directly determines the generation efficiency and selectivity of H2O2. Currently, conventional photocatalytic materials still suffer from many inherent defects, significantly hindering the industrialization of photocatalytic H2O2 production technology. Most semiconductor materials have weak visible light capture capabilities, only able to utilize ultraviolet light to excite the reaction, resulting in extremely low solar energy utilization. Simultaneously, photogenerated electron-hole pairs within the material readily recombine rapidly, drastically reducing the number of charge carriers effectively participating in the catalytic reaction, leading to slow reaction kinetics. Furthermore, single-material structures often exhibit poor stability, easily undergoing photocorrosion and particle agglomeration under illumination, resulting in short cycle life and an inability to precisely control the catalytic reaction pathway, leading to frequent redox side reactions and ultimately causing low H2O2 yield and poor selectivity.

[0004] Cu2O, CuS, and ZnIn2S4 are all high-quality visible-light-responsive semiconductor materials with band structures suitable for photocatalytic H2O2 production systems. They possess advantages such as inexpensive and readily available raw materials and abundant surface active sites, making them popular substrates in the field of photocatalysis. However, each of these three individual materials has performance limitations, making it difficult to achieve efficient and stable H2O2 production. To overcome the technical shortcomings of single materials, this invention constructs a Cu2O@CuS@ZnIn2S4 bilayer core-shell composite photocatalytic material. Relying on the synergistic effect of the interfaces of the three materials, it optimizes optical absorption and charge transport performance, effectively suppresses carrier recombination, and improves structural stability and H2O2 product selectivity. This effectively solves the industry pain points of low efficiency and poor stability in existing photocatalytic H2O2 production, providing a new and feasible technical solution for efficient H2O2 preparation. Summary of the Invention

[0005] To address the aforementioned issues, this invention provides a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material, its preparation method, and its applications. The preparation process of this invention is simple, easy to control, and has low production costs. The Cu2O@CuS@ZnIn2S4 bilayer core-shell composite structured photocatalytic material obtained exhibits high activity and excellent cycle stability.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material, comprising the following steps:

[0008] 1) Mix Cu(NO3)2·3H2O, L-ascorbic acid, C6H5O7Na3 and water to obtain a mixed solution;

[0009] 2) Mix the mixture obtained in step 1) with sodium hydroxide solution, stir, wash the precipitate and dry it to obtain Cu2O with a cubic structure;

[0010] 3) Disperse the cubic Cu2O obtained in step 2) in water to obtain a Cu2O dispersion;

[0011] 4) The Cu2O dispersion obtained in step 3) is mixed with Na2S solution and reacted. The precipitate is washed and dried to obtain Cu2O@CuS.

[0012] 5) Disperse the Cu2O@CuS obtained in step 4) in water to obtain a Cu2O@CuS dispersion;

[0013] 6) The Cu2O@CuS dispersion obtained in step 5) is mixed with Zn(CH3COO)2·2H2O, InCl3, and thioacetamide solution for hydrothermal reaction. The precipitate is washed and dried to obtain Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material.

[0014] Preferably, the volume ratio of Cu(NO3)2·3H2O, L-ascorbic acid, C6H5O7Na3, and water in step 1) is 0.4 mmol:0.04 mmol:0.4 mmol:100 mL.

[0015] Preferably, the volume ratio of the sodium hydroxide solution in step 2) to the water in step 1) is 1:50;

[0016] The concentration of the sodium hydroxide solution is 0.5 mol / L;

[0017] The stirring time is 30 minutes;

[0018] Wash the precipitate with water and ethanol;

[0019] The drying temperature is 60°C.

[0020] Preferably, in step 3), the mass ratio of the cubic Cu2O to the volume ratio of water is 20 mg: 30 mL.

[0021] Preferably, the volume ratio of the Na2S solution in step 4) to the mass ratio of the Cu2O with a cubic structure in step 3) is 10 mL: 20 mg;

[0022] The concentration of the Na₂S solution is 0.5 mol / L;

[0023] The reaction time is 2 hours;

[0024] Wash the precipitate with water and ethanol;

[0025] The drying temperature is 60°C.

[0026] Preferably, in step 5), the mass ratio of Cu2O@CuS to water is 20~40mg:40mL.

[0027] Preferably, in step 5), the mass ratio of Cu2O@CuS to water is 30 mg: 40 mL.

[0028] Preferably, the mass ratio of the amount of Zn(CH3COO)2·2H2O, the amount of InCl3, and the volume of the thioacetamide solution in step 6) to the mass ratio of Cu2O@CuS in step 5) is 0.4 mmol:0.8 mmol:20 mL:20~40 mg;

[0029] The concentration of the thioacetamide solution is 0.5 mol / L;

[0030] The conditions for the hydrothermal reaction include: a temperature of 180°C and a time of 12 hours.

[0031] Wash the precipitate with water and ethanol;

[0032] The drying temperature is 60°C.

[0033] The present invention also provides a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material prepared by the preparation method described above.

[0034] This invention also provides the application of the Cu2O@CuS@ZnIn2S4 double-layer core-shell structure photocatalytic material described in the above technical solution in the catalytic production of hydrogen peroxide under visible light.

[0035] The beneficial effects of this invention are:

[0036] (1) In this invention, Cu(NO3)2·3H2O, L-ascorbic acid, and C6H5O7Na3 are dissolved in deionized water and stirred for 30 minutes. Then, TAA solution is added, and the final product is washed three times with water and ethanol, respectively, and then dried under vacuum at 60°C to obtain Cu2O with a cubic structure. The Cu2O prepared above is dispersed in deionized water and ultrasonically stirred to form a uniformly dispersed suspension. Then, TAA solution is added and stirred for 30 minutes to obtain core-shell structured Cu2O@CuS. Finally, the Cu2O@CuS prepared above is dispersed in deionized water and ultrasonically stirred to form a uniformly dispersed suspension. Zn(CH3COO)2·2H2O and InCl3 are added to the dispersion, mixed evenly, and then TAA solution is added. The mixture is transferred to a polytetrafluoroethylene autoclave and kept at 180°C for 12 hours. After natural cooling, the product was washed with water and ethanol, and then dried in a vacuum oven at 60°C to finally obtain the Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material. The method of this invention is simple, has a short preparation time, low energy consumption, and the obtained Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material possesses abundant pore structure and a large specific surface area.

[0037] (2) The Cu2O@CuS@ZnIn2S4 bilayer core-shell structure material prepared in this invention was used as a photocatalyst, and its photocatalytic performance was evaluated by photocatalytic H2O2 production under an O2 atmosphere. The photocatalytic H2O2 production performance test data showed that the Cu2O@CuS@ZnIn2S4 bilayer core-shell composite material exhibited the best H2O2 production activity, significantly better than pure Cu2O, pure CuS, and pure ZnIn2S4 monomer materials. After the photocatalytic reaction, the photocatalytic H2O2 production rate of this composite material reached 7095.8 μmol·L⁻¹. -1 h -1 This is far higher than the 246.9 μmol·L⁻¹ of ZnIn₂S₄ alone. -1 h -1 133.6 μmol·L⁻¹ CuS -1 h -1 With Cu2O 62.8 μmol·L -1 h -1Compared to the single-component synthesis, the composite structure showed a 25-fold increase in yield, demonstrating the significant effect of multi-level core-shell heterojunctions on enhancing catalytic activity. Its superior performance stems from its compact interfacial structure, which effectively promotes photogenerated charge separation, suppresses electron-hole recombination, and mitigates the defects of monomer materials such as easy aggregation and photocorrosion. Furthermore, this material exhibits minimal yield decay during cycling tests, stably maintaining an efficient H2O2 generation pathway. Combining high catalytic activity with structural stability, it represents a high-performance visible-light photocatalytic H2O2 production material.

[0038] (3) The Cu2O@CuS@ZnIn2S4 double-layer core-shell structure material prepared by the present invention can effectively enhance the photocatalytic H2O2 production activity and cycle stability, and has broad development prospects. Attached Figure Description

[0039] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly described below.

[0040] Figure 1 The X-ray diffraction (XRD) patterns of the pure Cu2O, pure CuS, pure ZnIn2S4, Cu2O@CuS and Cu2O@CuS@ZnIn2S4 double-layer core-shell structure materials prepared in Example 1 of this invention are shown.

[0041] Figure 2 These are scanning electron microscope (SEM) images of (a) Cu2O, (b) CuS, (c) ZnIn2S4, (d) Cu2O@CuS and (e and f) Cu2O@CuS@ZnIn2S4 double-layer core-shell structured materials prepared in Example 2 of this invention;

[0042] Figure 3 This is a schematic diagram illustrating the photocatalytic activity of Cu2O, CuS, ZnIn2S4, Cu2O@CuS and Cu2O@CuS@ZnIn2S4 bilayer core-shell structure materials prepared in Example 1 of the present invention for the photocatalytic preparation of H2O2.

[0043] Figure 4 This is a schematic diagram of the H2O2 production activity of the Cu2O@CuS@ZnIn2S4-X double-layer core-shell structure material prepared in Example 2 of this invention under visible light irradiation;

[0044] Figure 5 This is a schematic diagram illustrating the cycle stability of the Cu2O@CuS@ZnIn2S4 double-layer core-shell structure material prepared in Example 2 of this invention for the catalytic preparation of H2O2 under light irradiation. Detailed Implementation

[0045] This invention provides a method for preparing a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material, comprising the following steps:

[0046] 1) Mix Cu(NO3)2·3H2O, L-ascorbic acid, C6H5O7Na3 and water to obtain a mixed solution;

[0047] 2) Mix the mixture obtained in step 1) with sodium hydroxide solution, stir, wash the precipitate and dry it to obtain Cu2O with a cubic structure;

[0048] 3) Disperse the cubic Cu2O obtained in step 2) in water to obtain a Cu2O dispersion;

[0049] 4) The Cu2O dispersion obtained in step 3) is mixed with Na2S solution and reacted. The precipitate is washed and dried to obtain Cu2O@CuS.

[0050] 5) Disperse the Cu2O@CuS obtained in step 4) in water to obtain a Cu2O@CuS dispersion;

[0051] 6) The Cu2O@CuS dispersion obtained in step 5) is mixed with Zn(CH3COO)2·2H2O, InCl3, and thioacetamide solution for hydrothermal reaction. The precipitate is washed and dried to obtain Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material.

[0052] This invention involves mixing Cu(NO3)2·3H2O, L-ascorbic acid, C6H5O7Na3, and water to obtain a mixed solution. In this invention, the preferred volume ratio of Cu(NO3)2·3H2O, L-ascorbic acid, C6H5O7Na3, and water is 0.4 mmol:0.04 mmol:0.4 mmol:100 mL.

[0053] This invention involves mixing and stirring the aforementioned mixture with a sodium hydroxide solution, washing the resulting precipitate, and then drying it to obtain Cu₂O with a cubic structure. In this invention, the preferred volume ratio of the sodium hydroxide solution to the water is 1:50. The preferred concentration of the sodium hydroxide solution is 0.5 mol / L. The preferred stirring time is 30 min. It is preferred to use water and ethanol to wash the precipitate. The preferred drying temperature is 60°C.

[0054] This invention disperses the cubically structured Cu2O in water to obtain a Cu2O dispersion. In this invention, the preferred mass ratio of the cubically structured Cu2O to the volume ratio of water is 20 mg:30 mL.

[0055] In this invention, the Cu2O dispersion is mixed with a Na2S solution and reacted. The resulting precipitate is washed and then dried to obtain Cu2O@CuS. In this invention, the volume ratio of the Na2S solution to the mass ratio of the cubic Cu2O is 10 mL:20 mg. In this invention, the concentration of the Na2S solution is preferably 0.5 mol / L. In this invention, the reaction time is preferably 2 hours. In this invention, water and ethanol are preferably used to wash the precipitate. In this invention, the drying temperature is preferably 60°C.

[0056] This invention disperses Cu2O@CuS in water to obtain a Cu2O@CuS dispersion. In this invention, the preferred mass-to-volume ratio of Cu2O@CuS to water is 20-40 mg:40 mL. In this invention, the preferred mass-to-volume ratio of Cu2O@CuS to water is 30 mg:40 mL.

[0057] This invention involves a hydrothermal reaction of a Cu2O@CuS dispersion with Zn(CH3COO)2·2H2O, InCl3, and a thioacetamide solution. The resulting precipitate is washed and dried to obtain a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material. In this invention, the preferred mass ratio of Zn(CH3COO)2·2H2O, InCl3, thioacetamide solution, and Cu2O@CuS is 0.4 mmol:0.8 mmol:20 mL:20~40 mg. The preferred concentration of the thioacetamide solution is 0.5 mol / L. The preferred hydrothermal reaction conditions include a temperature of 180°C and a time of 12 h. The precipitate is preferably washed with water and ethanol. The preferred drying temperature is 60°C.

[0058] The present invention also provides a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material prepared by the preparation method described above.

[0059] This invention also provides the application of the Cu2O@CuS@ZnIn2S4 double-layer core-shell structure photocatalytic material described in the above technical solution in the catalytic production of hydrogen peroxide under visible light.

[0060] To further illustrate the present invention, the following detailed description is provided in conjunction with embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0061] Example 1

[0062] A method for preparing a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material, comprising the following steps:

[0063] S1. Dissolve 0.4 mmol Cu(NO3)2·3H2O, 0.04 mmol L-ascorbic acid and 0.4 mmol C6H5O7Na3 in 100 mL of deionized water and stir vigorously.

[0064] S2. After forming a homogeneous solution, add 2 ml of 0.5 mol / L NaOH solution dropwise. After stirring for 30 minutes, wash the product with water and ethanol, and then dry it in a vacuum oven at 60℃ to finally obtain Cu2O with a cubic structure.

[0065] S3. Disperse 20 mg of the cubic Cu2O prepared above in 30 ml of deionized water, sonicate and stir to form a uniformly dispersed suspension, then add 10 ml of 0.5 mol / L Na2S·9H2O solution, stir vigorously for 2 h, wash the precipitate thoroughly with water and ethanol, and dry in a vacuum drying oven at 60℃ to obtain Cu2O@CuS core-shell structure powder sample.

[0066] S4. Disperse 20 mg of the prepared Cu2O@CuS core-shell structure in 40 ml of deionized water, and sonicate to form a uniform suspension. Then add 0.4 mmol of Zn(CH3COO)2·2H2O, 0.8 mmol of InCl3, and 20 ml of 0.5 mol / L TAA (thioacetamide). Transfer the solution to a 100 ml stainless steel autoclave and maintain it at 180 °C for 12 h. After naturally cooling to room temperature, wash the precipitate thoroughly with water and ethanol, and dry it in a vacuum drying oven at 60 °C to obtain a Cu2O@CuS@ZnIn2S4 double-layer core-shell structure powder sample, named Cu2O@CuS@ZIS-1.

[0067] Example 2

[0068] A method for preparing a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material, comprising the following steps:

[0069] S1. Dissolve 0.4 mmol Cu(NO3)2·3H2O, 0.04 mmol L-ascorbic acid and 0.4 mmol C6H5O7Na3 in 100 mL of deionized water and stir vigorously.

[0070] S2. After forming a homogeneous solution, add 2 ml of 0.5 mol / L NaOH solution dropwise. After stirring for 30 minutes, wash the product with water and ethanol, and then dry it in a vacuum oven at 60℃ to finally obtain Cu2O with a cubic structure.

[0071] S3. Disperse 20 mg of the cubic Cu2O prepared above in 30 ml of deionized water, sonicate and stir to form a uniformly dispersed suspension, then add 10 ml of 0.5 mol / L Na2S·9H2O solution, stir vigorously for 2 h, wash the precipitate thoroughly with water and ethanol, and dry in a vacuum drying oven at 60℃ to obtain Cu2O@CuS core-shell structure powder sample.

[0072] S4. Disperse 30 mg of the prepared Cu2O@CuS core-shell structure in 40 ml of deionized water, sonicate to form a uniform suspension, then add 0.4 mmol of Zn(CH3COO)2·2H2O, 0.8 mmol of InCl3, and 20 ml of 0.5 mol / L TAA (thioacetamide). Then, transfer the solution to a 100 ml stainless steel autoclave and maintain it at 180 °C for 12 h. After naturally cooling to room temperature, wash the precipitate thoroughly with water and ethanol, and dry it in a vacuum drying oven at 60 °C to obtain a Cu2O@CuS@ZnIn2S4 bilayer core-shell structure powder sample, named Cu2O@CuS@ZIS-2.

[0073] Example 3

[0074] A method for preparing a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material, comprising the following steps:

[0075] S1. Dissolve 0.4 mmol Cu(NO3)2·3H2O, 0.04 mmol L-ascorbic acid and 0.4 mmol C6H5O7Na3 in 100 mL of deionized water and stir vigorously.

[0076] S2. After forming a homogeneous solution, add 2 ml of 0.5 mol / L NaOH solution dropwise. After stirring for 30 minutes, wash the product with water and ethanol, and then dry it in a vacuum oven at 60℃ to finally obtain Cu2O with a cubic structure.

[0077] S3. Disperse 20 mg of the cubic Cu2O prepared above in 30 ml of deionized water, sonicate and stir to form a uniformly dispersed suspension, then add 10 ml of 0.5 mol / L Na2S·9H2O solution, stir vigorously for 2 h, wash the precipitate thoroughly with water and ethanol, and dry in a vacuum drying oven at 60℃ to obtain Cu2O@CuS core-shell structure powder sample.

[0078] S4. Disperse 40 mg of the prepared Cu2O@CuS core-shell structure in 40 ml of deionized water, and sonicate to form a uniformly dispersed suspension. Then add 0.4 mmol of Zn(CH3COO)2·2H2O, 0.8 mmol of InCl3, and 20 ml of 0.5 mol / L TAA (thioacetamide). Transfer the solution to a 100 ml stainless steel autoclave and maintain at 180 °C for 12 h. After naturally cooling to room temperature, wash the precipitate thoroughly with water and ethanol, and dry in a vacuum drying oven at 60 °C to obtain a Cu2O@CuS@ZnIn2S4 double-layer core-shell structure powder sample, named Cu2O@CuS@ZIS-3.

[0079] Performance testing:

[0080] 1. The phase structure of the Cu2O@CuS@ZnIn2S4 double-layer core-shell composite photocatalytic materials prepared in Examples 1-3 was analyzed using an XRD instrument.

[0081] Figure 1 The XRD patterns of pure Cu₂O, pure CuS, pure ZnIn₂S₄, Cu₂O@CuS, and Cu₂O@CuS@ZnIn₂S₄ double-layer core-shell structured materials prepared in Examples 1-3 are shown, used to characterize the crystal structures of different materials. Figure 1 As shown, XRD pattern analysis results indicate that pure Cu2O, CuS, and ZnIn2S4 samples all exhibit their respective characteristic diffraction peaks, with sharp peak shapes and no impurity peaks, proving that the prepared single-component materials have good crystallinity and high purity. The XRD pattern of the Cu2O@CuS@ZnIn2S4 bilayer core-shell composite material simultaneously shows characteristic diffraction peaks of the three matrix materials, without any new impurity peaks, indicating that no impurities were introduced during the composite process, and the crystal structures of each component were completely preserved. The composite material's diffraction peak intensity showed no significant attenuation and peak position shift, confirming the successful construction of the multilayer composite structure and that the heterojunction composite method did not damage the crystal framework of the individual materials. Furthermore, the absence of obvious crystal phase defect peaks in the spectrum indicates that the bilayer core-shell structure has excellent crystallinity, providing a stable structural basis for photocatalytic reactions and contributing to improved cycle stability and catalytic activity in the photocatalytic production of H2O2.

[0082] 2. The microstructures of the (a) Cu2O, (b) CuS, (c) ZnIn2S4, (d) Cu2O@CuS and (e and f) Cu2O@CuS@ZnIn2S4 double-layer core-shell structured materials prepared in Example 1 were analyzed by SEM.

[0083] Figure 2 SEM images of (a) Cu2O, (b) CuS, (c) ZnIn2S4, (d) Cu2O@CuS and (e and f) Cu2O@CuS@ZnIn2S4 double-layer core-shell structured materials prepared in Example 1, wherein... Figure 2 (a) and (b) are SEM images of pure-phase Cu₂O and CuS, respectively. It can be seen that both have a cubic structure with an average diameter of approximately 600 nm. The cubic structure of Cu₂O has a relatively smooth surface without obvious wrinkles. In contrast, the cubic structure of CuS exhibits obvious wrinkles and uneven, sheet-like layers resulting from etching. ZnIn₂S₄ has a two-dimensional nanosheet structure with non-uniform dimensions, but its diameter ranges from 500 nm to 1 μm. Its surface is relatively smooth and contains irregular granular material; no porous structure was observed. When a Cu₂O@CuS core-shell structure is formed, the overall structure still exhibits a cubic structure, with an uneven, sheet-like texture after etching, and an average diameter of approximately 600 nm. Furthermore, when a Cu₂O@CuS@ZnIn₂S₄ composite material is formed, the overall structure still exhibits a cubic structure. The surface is coated with a thin film, and some of the particles form columnar or pointed structures that stand upright on the surface. This not only enhances light absorption and utilization, but also effectively shortens the charge transport distance and accelerates charge transport, ultimately enhancing the photocatalytic activity for H2O2 production.

[0084] 3. The photocatalytic H2O2 production performance of the Cu2O@CuS@ZnIn2S4 bilayer core-shell structured materials prepared in Examples 1-3 was analyzed using gas chromatography and a Labsolar-6a all-glass automated online trace gas analysis system.

[0085] Figure 3The photocatalytic performance of Cu2O, CuS, ZnIn2S4, Cu2O@CuS, and Cu2O@CuS@ZnIn2S4 nanomaterials prepared in Example 1 for H2O2 production was evaluated. Specifically, the H2O2 production activity of the prepared photocatalysts was assessed under visible light irradiation and an O2 atmosphere. Under specific experimental conditions, the photocatalytic reaction was carried out in a gas-closed system, with the reactor made of quartz. The photocatalytic instrument used was a Labsolar-6a all-glass automated online trace gas analysis system from Beijing Perfect Light Technology Co., Ltd. The light source was a 300 W xenon lamp, using filters with wavelengths of (420 nm < λ < 780 nm) and an Analogue Sunlight AM1.5G filter, respectively. In a typical experiment, Cu2O@CuS@ZnIn2S4 (0.05 g) was added to the photoreactor, followed by 10 mL of C2H5OH and 190 mL of deionized water, and then the mixture was ultrasonically stirred for 10 minutes until homogeneous. Then, O2 was continuously introduced into the suspension (in an oxygen atmosphere) to irradiate it. Performance data of photocatalytic H2O2 production showed that different catalytic materials exhibited significantly different hydrogen peroxidation activities under the same visible light irradiation conditions. Among them, the Cu2O@CuS@ZnIn2S4 double-layer core-shell composite material showed the best catalytic performance, with overall activity significantly better than pure Cu2O, pure CuS, and pure ZnIn2S4 single-component materials. Quantitative test results showed that after irradiation, the H2O2 production rate of the Cu2O monomer was only 62.8 μmol·L⁻¹. -1 h -1 The yield of pure CuS sample was 133.6 μmol·L⁻¹. -1 h -1 The yield of pure ZnIn2S4 sample was 246.9 μmol·L⁻¹. -1 h -1 Overall, the H2O2 production capacity of the three types of monomer materials was relatively low. In contrast, the photocatalytic H2O2 production of Cu2O@CuS was partially enhanced, which is attributed to the synergistic effect of the core-shell structure and the heterojunction. When a Cu2O@CuS@ZnIn2S4-2 bilayer core-shell structure material was formed, the photocatalytic activity was further enhanced, achieving an average H2O2 production rate of 7095.8 μmol·L⁻¹ within 5 hours. -1 h -1 The activity enhancement effect is extremely significant. Figure 4(The performance of three examples is explained). The reason for this is that the bilayer core-shell heterostructure can fully leverage the synergistic effect of the three semiconductor materials, effectively optimizing visible light absorption and significantly improving photon utilization. Simultaneously, the constructed multi-level heterojunction interface provides a rapid migration channel for photogenerated carriers, significantly suppressing disordered recombination of electrons and holes, improving effective charge utilization, and significantly accelerating the kinetics of interfacial catalytic reactions. Furthermore, the compact bilayer core-shell structure effectively alleviates the particle agglomeration and photocorrosion problems commonly found in monomer materials, stabilizing the material's microstructure and ensuring the continuous and efficient catalytic reaction. In summary, this composite material, with its superior structural advantages and electronic control capabilities, achieves efficient and stable photocatalytic H2O2 production.

[0086] Figure 4 As shown, the photocatalytic activity of Cu2O@CuS@ZnIn2S4-X (X=1, 2, and 3) composite materials synthesized under different transformation conditions first increased and then decreased. The photocatalytic H2O2 production rate of Cu2O@CuS@ZnIn2S4-1 reached 6289.6 μmol·L⁻¹ after 5 hours of visible light irradiation. -1 h -1 The photocatalytic H2O2 production rate of Cu2O@CuS@ZnIn2S4-3 reached 6897.2 μmol·L after 5 hours of visible light irradiation. -1 h -1 By comparing the structures, it can be seen that Cu2O@CuS@ZnIn2S4-2 achieves the best activity.

[0087] like Figure 5 As shown, and more importantly, a cyclic stability experiment was conducted under visible light irradiation, with each cycle lasting five hours, to evaluate the stability of the Cu2O@CuS@ZnIn2S4 bilayer core-shell composite material in the photocatalytic H2O2 production process. Under visible light irradiation, the average rate of H2O2 production by Cu2O@CuS@ZnIn2S4-2 photocatalytic production reached 7096.2 μmol L⁻¹ in the first cycle. -1 h -1 As the cycle time increased, its photocatalytic H2O2 production activity decreased, and after the fifth cycle, its average photocatalytic H2O2 production rate reached 6505.8 μmol L⁻¹. -1 h -1 This represents 91.7% of the initial cycle yield. Therefore, based on the above analysis, Cu2O@CuS@ZnIn2S4-2 not only exhibits high photocatalytic activity for H2O2 production but also demonstrates excellent cycle durability, making it a promising candidate photocatalyst for H2O2 production.

[0088] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material, characterized in that, Includes the following steps: 1) Mix Cu(NO3)2·3H2O, L-ascorbic acid, C6H5O7Na3 and water to obtain a mixed solution; 2) Mix the mixture obtained in step 1) with sodium hydroxide solution, stir, wash the precipitate and dry it to obtain Cu2O with a cubic structure; 3) Disperse the cubic Cu2O obtained in step 2) in water to obtain a Cu2O dispersion; 4) The Cu2O dispersion obtained in step 3) is mixed with Na2S solution and reacted. The precipitate is washed and dried to obtain Cu2O@CuS. 5) Disperse the Cu2O@CuS obtained in step 4) in water to obtain a Cu2O@CuS dispersion; 6) The Cu2O@CuS dispersion obtained in step 5) is mixed with Zn(CH3COO)2·2H2O, InCl3, and thioacetamide solution for hydrothermal reaction. The precipitate is washed and dried to obtain Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material.

2. The preparation method according to claim 1, characterized in that, Step 1) The volume ratio of Cu(NO3)2·3H2O, L-ascorbic acid, C6H5O7Na3 and water is 0.4mmol:0.04mmol:0.4mmol:100mL.

3. The preparation method according to claim 1, characterized in that, The volume ratio of the sodium hydroxide solution in step 2) to the water in step 1) is 1:50; The concentration of the sodium hydroxide solution is 0.5 mol / L; The stirring time is 30 minutes; Wash the precipitate with water and ethanol; The drying temperature is 60°C.

4. The preparation method according to claim 1, characterized in that, Step 3) The mass ratio of the cubic Cu2O to the volume ratio of water is 20 mg: 30 mL.

5. The preparation method according to claim 1, characterized in that, In step 4), the volume ratio of the Na2S solution to the Cu2O with a cubic structure in step 3) is 10 mL: 20 mg. The concentration of the Na₂S solution is 0.5 mol / L; The reaction time is 2 hours; Wash the precipitate with water and ethanol; The drying temperature is 60°C.

6. The preparation method according to claim 1, characterized in that, Step 5) The mass ratio of Cu2O@CuS to water is 20~40mg:40mL.

7. The preparation method according to claim 1 or 6, characterized in that, Step 5) The mass ratio of Cu2O@CuS to water is 30 mg: 40 mL.

8. The preparation method according to claim 1, characterized in that, The mass ratio of the amount of Zn(CH3COO)2·2H2O, the amount of InCl3, and the volume of the thioacetamide solution in step 6) to the mass ratio of Cu2O@CuS in step 5) is 0.4 mmol: 0.8 mmol: 20 mL: 20~40 mg. The concentration of the thioacetamide solution is 0.5 mol / L; The conditions for the hydrothermal reaction include: a temperature of 180°C and a time of 12 hours. Wash the precipitate with water and ethanol; The drying temperature is 60°C.

9. A Cu2O@CuS@ZnIn2S4 bilayer core-shell structured photocatalytic material prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the Cu2O@CuS@ZnIn2S4 bilayer core-shell structure photocatalytic material according to claim 9 in the catalytic production of hydrogen peroxide under visible light.